Impaired resistance and enhanced pathology during infection with a noninvasive, attaching-effacing enteric bacterial pathogen, Citrobacter rodentium, in mice lacking IL-12 or IFN-gamma - Simmons, Cameron (2018)
Mice infected with Citrobacter rodentium represent an excellent model in which to examine immune defenses against an attaching-effacing enteric bacterial pathogen. Colonic tissue from mice infected with C. rodentium harbors increased transcripts for IL-12 and IFN-gamma and displays mucosal pathology compared with uninfected controls. In this study, the role of IL-12 and IFN-gamma in host defense and mucosal injury during C. rodentium infection was examined using gene knockout mice. IL-12p40(-/-) and IFN-gamma(-/-) mice were significantly more susceptible to mucosal and gut-derived systemic C. rodentium infection. In particular, a proportion of IL-12p40(-/-) mice died during infection. Analysis of the gut mucosa of IL-12p40(-/-) mice revealed an influx of CD4(+) T cells and a local IFN-gamma response. Infected IL-12p40(-/-) and IFN-gamma(-/-) mice also mounted anti-Citrobacter serum and gut-associated IgA responses and strongly expressed inducible NO synthase (iNOS) in mucosal tissue, despite diminished serum nitrite/nitrate levels. However, iNOS does not detectably contribute to host defense against C. rodentium, as iNOS(-/-) mice were not more susceptible to infection. However, C57BL/6 mice infected with C. rodentium up-regulated expression of the mouse beta-defensin (mBD)-1 and mBD-3 in colonic tissue. In contrast, expression of mBD-3, but not mBD-1, was significantly attenuated during infection of IL-12- and IFN-gamma-deficient mice, suggesting mBD-3 may contribute to host defense. These studies are among the first to examine mechanisms of host resistance to an attaching-effacing pathogen and show an important role for IL-12 and IFN-gamma in limiting bacterial infection of the colonic epithelium.